Key aspects of financial literacy - Nurgazina, A. M. (Journal of Economic Research & Business Administration, 2016)
Financial literacy has become one of the most important priorities for the social and financial development of many countries. This item attracted high attention of global society from mid 1990-s providing implementation of the short-term regional programs in some countries. Steady growth of the world’s economy and financial system as well as economies of developed and emerging markets had been averted by global threats and financial crises leading to a necessity to improve financial culture and illiteracy among the population in the beginning of 2000-s. As a result many countries developed mid-term policy to create a certain system of the basic financial education. The same concept in fact was used in Kazakhstan. Financial literacy has become one of the most important items in creation of sustainable financial system. State programs aimed to provide tools for the increase of the level of financial literacy for the citizens. Central bank is a body that is responsible for the financial literacy and financial services’ consumers rights protection.